Making meanings, creating family intertextuality and framing in family interaction - Gordon, Cynthia, 1975- (New York ; Oxford : Oxford University Press, 2009)
Cynthia Gordon uses tape-recorded conversations about everyday, mundane topics among three dual-income families to explore how family communication creates a special kind of meaning and a sense of distinctive group coherence within the family.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Communication in the family -- United States -- Case studies; Discourse analysis -- United States